2011
DOI: 10.4028/www.scientific.net/amr.314-316.66
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Hot Bending of 22MnB5 Steel

Abstract: Special V-shaped heat bending test was designed for 22MnB5 hot forming steel of different thicknesses. Blanks after heating 5 min at around 950°C to austenize fully were bended at different temperature conditions, and simultaneously the spring-back behavior and microstructure features of heat bending specimens were investigated. The result shows that 600-650°C temperature zone is optimal for bending forming and martensite texture transforming. Real hot forming anti-collision beams were produced at 600-650°C an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Not only the starting temperature of martensite, but also the amount of martensite decreased by applying higher strain and higher force level. Guo et al [2] studied some basic properties and applications of hot stamping steel for vehicles, and obtained basic mechanical properties such as tensile strength, bending strength and stress-strain relationships of 22MnB5, and obtained key process parameters in the hot stamping process. Hou et al [3] studied the effects of heating temperature on the microstructures and austenite grains of 22MnB5, and found that with the increase of heating temperature, the width of martensite lath bundle and austenite grain size of sheet microstructure increase.…”
Section: Introductionmentioning
confidence: 99%
“…Not only the starting temperature of martensite, but also the amount of martensite decreased by applying higher strain and higher force level. Guo et al [2] studied some basic properties and applications of hot stamping steel for vehicles, and obtained basic mechanical properties such as tensile strength, bending strength and stress-strain relationships of 22MnB5, and obtained key process parameters in the hot stamping process. Hou et al [3] studied the effects of heating temperature on the microstructures and austenite grains of 22MnB5, and found that with the increase of heating temperature, the width of martensite lath bundle and austenite grain size of sheet microstructure increase.…”
Section: Introductionmentioning
confidence: 99%